Pengaruh Pemberian Tablet Tambah Darah terhadap Kadar Hemoglobin Siswi SMA 5 Kota Ternate - Richa Novyana Hardianti; Nikma Nikma (Poltekkes Kemenkes Padang, 2024)
Efforts to prevent anemia in adolescents through the supplementation of Blood Additive Tablets in adolescent girls is a very strategic, specific intervention to prepare healthy prospective mothers. The aim was to know the effect of giving blood supplement tablets on the hemoglobin levels of female high school students in Ternate City 5. The design was Quasi Experimental with a One Group Posttest. The samples were female students aged 15-18 years at SMA 5 Ternate with a total of 106 samples taken using the Slovin formula. The research instrument consists of an explanation sheet, a letter of consent, general questionnaire, screening questionnaire, hemoglobin examination tool. All independent variables in the form of categorical data were analyzed for influence using the Paire sample T-test. Before being given blood supplement tablets, only 26 respondents (25%) had normal hemoglobin levels. After being given blood supplement tablets, the respondents' normal hemoglobin levels increased, 78 people (74%). The P value is 0.008 < 0.05, indicating that there is an influence between before and after hemoglobin levels using blood supplement tablets. The results obtained indicate that administering blood supplement tablets can increase hemoglobin levels in research subjects. In conclusion, giving blood supplement tablets can help increase hemoglobin levels in SMA 5 Ternate students. Therefore, there needs to be cooperation between schools, local governments and parents to prevent health problems such as anemia in young women.